Comparative Study between Aluminium Sulphate and Moringa Oleifera Seeds as Coagulants in Drinking water Treatment (University of Khartoum Engineering Journal, 2022)
This study is a laboratory based study comparing the efficiency of Alum with Moringa seeds as coagulants in order to treat the water samples from Blue Nile River in Blue Nile State. The samples turbidities were 8580 NTU, 3000 NTU and 29.4 NTU from different sites. Six different doses for each coagulant and for each sample were used in Jar test apparatus with six- paddle gang stirrer. The initial turbidity 8580 NTU was reduced by 99.5% when used 150 ppm Alum. Meanwhile, Moringacoagulant gave 99.8% removal when using 130 ppm. The pH was decreased from 7.9 to 7.36 corresponding to Alum dose with increasing in EC and TDS but was in acceptable levels. With Moringa the pH, EC and TDS were insignificantly changed. The taste and color in both coagulants were unsuitable while the odor was acceptable. In the sample 3000 NTU, the best activity at 100ppm Alum. Achieved 90% reduction in turbidity load and 99.4% reduction at 100 ppm Moringa. The pH in Alum. Also started to fall down from 7.61 to 6.8, in Moringa no significant change was occurred. The EC, TDS, odor and taste were not affected with used doses. The color still unsuitable for consumer in both coagulants. In sample 29.4 NTU the Alum coagulant enhanced theturbidity removal till to 95.4% when 50 ppm was used, while in 10 ppm Moringa, reduced the turbidity by 87.9%. The other characteristics color, odor and taste were acceptable at both coagulants with no significant change in EC and TDS
Keywords: Aluminum; Moringa; pH; EC; TDS; color; odor; taste; Blue Nile